THE CONTRIBUTION OF THE FISHERIES SUB SECTOR OF THE ECONOMY AND LABOR FORCE ABSORPTION AT SIBOLGA CITY IN NORTH SUMATERA PROVINCE - Siregar, Ahmad Kurniawan; Bathara, Lamun; ', Hendrik (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
ABSTRACTThis research was conducted on September - October 2014 in Sibolga City of North Sumatra Province. The method used was a survey by analyzing secondary data, the data used is the chain of data (time series data) of the 2009 to 2013. The purpose of this study is to determine the contribution of the fisheries sub-sector of the economy and labor force absorption, knowing whether the fisheries sub-sector and fisheries sub-sector labor force classified base or no base , and to determine the impact of the fisheries sub-sector of the economy and labor force absorption.Based on the results of the study showed that the fisheries sub-sector contributions from the 2009 to 2013 ranges from 23.45% - 24.10% and the absorption of the labor force ranges from 23.9% - 37.0%. During the period 2009 - 2013 the value of Location Quotient (LQ) fisheries sub-sector ranged from 9.18 to 9.65. and the value of Location Quotient (LQ) labor force ranged from 8.7 to 10.9. During the period 2009 - 2013 the value of the Multiplier Effect fisheries sub-sector ranged from 3.52 to 6.40. And value Multiplier Effect fisheries sub-sector labor force ranged from 0.9 to 1.6.Key Words : Contribution, Base dan Multiplier Effect